De la contingence et de la carrière - Marie-Ange Schiltz (Genre, Sexualité et Société)
This is the story of a career devoted to gathering and interpreting quantitative information on human behavior. The manipulation of figures, tables, graphs and statistical formulas, more or less reliable according to the technique of construction of the sample considered, directs the general direction of the research. Whatever the sophistication of the techniques used, the author never loses sight of that human behaviors in society are numerous, uncertain, and sometimes aberrant against the standards. Then, there is the awareness that the quantitative approach is dependent on the practices of classification and categorization strongly influenced by social representations. This situation is particularly critical in the case of deviant behavior and minority. Given the intricacies of human behavior, there can’t be very truth in the numbers or confidence in the conclusions. Knowledge of social life can only be established in reference to the probability theory that establishes the degree of lifelikeness of the speech. With the usual caveats about the limits and reliability of observation, from signs, traces and tracks, a cautious and vague discourse ("almost always", "more often" slightly below "significant minority"), handled with rigor, may advance findings more probable than others.